2019
DOI: 10.1177/0363546519888909
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of the Latarjet Procedure for the Treatment of Chronic Anterior Shoulder Instability: Patients With Prior Arthroscopic Bankart Repair Versus Primary Cases

Abstract: Background: It remains unclear whether results differ between a Latarjet procedure performed after a failed arthroscopic Bankart repair and one performed as the primary operation. Purpose: To compare the postoperative outcomes of the Latarjet procedure when performed as primary surgery and as revision for a failed arthroscopic Bankart repair. Study Design: Cohort study; Level of evidence, 3. Methods: A multicenter retrospective comparative case-cohort analysis was performed for all patients undergoing a Latarj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 36 publications
3
43
1
1
Order By: Relevance
“… 12 Another multicenter study including 308 patients undergoing the Latarjet reported that 91.5% of participants were competitive or recreational athletes. 33 In the current study, only 5 of 17 female patients (29.4%) who underwent the Latarjet procedure were injured during athletic participation. This indicates that sex-related differences may exist in the mechanism of injury and postoperative expectations among male and female patients who undergo the Latarjet procedure.…”
Section: Discussionmentioning
confidence: 65%
“… 12 Another multicenter study including 308 patients undergoing the Latarjet reported that 91.5% of participants were competitive or recreational athletes. 33 In the current study, only 5 of 17 female patients (29.4%) who underwent the Latarjet procedure were injured during athletic participation. This indicates that sex-related differences may exist in the mechanism of injury and postoperative expectations among male and female patients who undergo the Latarjet procedure.…”
Section: Discussionmentioning
confidence: 65%
“…The Latarjet procedure has been shown to be a viable procedure for patients with a failed prior stabilization, with previous studies showing similar results to those in patients with primary instability. 24 , 25 Although it is unclear how a prior failed ABR affects the outcomes of ABRR, further soft-tissue damage may predispose these patients to a higher risk of failure. 26 Both procedures appear to result in similar outcomes with their appropriate indications, but surgeons should be cautioned about choosing ABRR in patients with severe glenoid bone loss until this is better defined.…”
Section: Discussionmentioning
confidence: 99%
“…87 Forty-four studies reported the number of prior dislocations, which ranged from 2.2 51 to 40 93 dislocations. Three studies compared primary and revision surgery 86,100,101 ; 30 studies or study arms included only patients having primary surgery; and seven only included those having revision surgery (Supplementary Table 2). 30,58,64,75,78,102,103 RADIOGRAPHIC FINDINGS Roughly a third of included studies (29/92, 32.5%) measured postoperative arthritis, and an additional eight studies measured postoperative arthropathy.…”
Section: Demographics and Baseline Characteristicsmentioning
confidence: 99%
“…Nine studies reported the rate of recurrent instability without specifically defining instability as redislocation. 40,46,50,64,69,76,90,100,106,111 Among the 69 studies that used the coracoid bone and specifically reported redislocations, the majority (47/ 69,75.3%) reported patients experiencing either a single redislocation or no redislocation. Noticeably higher rates of postoperative instability were reported in studies of at-risk patient populations; 42.9% (6/14) of patients with epilepsy, 33 33.3% (3/9) of patients with seizure disorders, 34 and 48.0% (12/25) of patients with chronic locked anterior shoulder dislocations experienced postoperative instability.…”
Section: Recurrent Instabilitymentioning
confidence: 99%